Efficacy of Laparoscopic Hepatectomy versus Open Surgery for Hepatocellular Carcinoma With Cirrhosis: A Meta-analysis of Case-Matched Studies - Pan, Yu; Xia, Shunjie; Cai, Jiaqin; Chen, Ke; Cai, Xiujun (Frontiers in Oncology, 2021)
Background: The role of laparoscopic hepatectomy (LH) for hepatocellular carcinomas (HCC) with cirrhosis remains controversial and needs to be further assessed. The present meta-analysis aims to compare the surgical and oncological outcomes of LH to open hepatectomy (OH) for HCCs with cirrhosis. Methods: The Pubmed, Embase, and Cochrane Library were searched for studies comparing LH and OH from the date of inception to May 2020. Weighted mean differences (WMDs), odds ratios (ORs) and hazard ratios (HRs) were calculated for continuous variables, dichotomous variables and long-term variables, respectively, with 95% confidence intervals (CIs). Subgroup analysis was performed based on different resection types: major resection and minor resection. This meta-analysis was performed using the STATA 12.0 statistical software. Results: A total of 11 case-matched studies and one randomized clinical trial (522 patients in the LH group and 777 patients in the OH group) were included in this meta-analysis. For primary outcomes, LH was associated with decreases in overall complication rate (P <0.01), major complication rate (P <0.01), postoperative mortality (P <0.01), 1-y overall survival (OS) rate (HR P <0.01), 2-y OS ( P =0.02), 5-y OS (P <0.01) and 1-y disease free survival (DFS) rate (P = 0.01). For secondary outcomes, blood loss (P <0.01), transfusion rate (P = 0.02), length of hospitalization (LOH) (P <0.01), minor complication rate (P = 0.01), postoperative ascites (P <0.01) was lower in LH as comparing with OH. No significant differences in operation time (P = 0.52), postoperative liver failure (P = 0.09), 2-y DFS rate (P=0.06) and 5-y DFS rate (P = 0.18) were noted between LH and OH. Subgroup analysis of minor resection revealed LH retrieved similar favored outcomes in comparison with those in overall pooled analysis. However, LH had a longer operation time compared with OH in the setting of major resection (P <0.01). Conclusion: LH is technically feasible and safe for selected HCC patients with cirrhosis. LH can achieve favored short-term outcomes and long-term oncological outcomes in minor liver resection. LMH appears to offer some advantages compared to open approach, but concerns on surgical and oncological safety remain.